Comparative Analysis of Diagnostic Plague Antiphage Sera Received from Producers of Different Types - T. V. Alenkina; G. G. Krasichkov; G. M. Fomina; O. A. Lobovikova; N. P. Mironova; O. S. Pudenkova; A. K. Nikiforov; L. V. Sayapina; A. N. Malakhaeva (Проблемы особо опасных инфекций, 2010)
Manufacturing process of ovine hyperimmune sera against Pokrovskaya plague bacteriophage was worked out. Their stability in the process of storage was studied. Sera received were used as raw material to produce three experimental series of diagnostic plague antiphage ovine dry serum. Physicochemical properties, specific activity and specificity of the developed preparation were evaluated in comparison with similar commercial preparation produced from the equine serum. Similarity of all test parameters was revealed that enabled to recommend diagnostic plague antiphage ovine serum for application.